2000
DOI: 10.1074/jbc.275.17.12410
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of Active Thrombin-activable Fibrinolysis Inhibitor Takes Place by a Process That Involves Conformational Instability Rather Than Proteolytic Cleavage

Abstract: Thrombin-activable fibrinolysis inhibitor (TAFI) is present in the circulation as an inactive zymogen.Thrombin converts TAFI to a carboxypeptidase B-like enzyme (TAFIa) by cleaving at Arg 92 in a process accelerated by the cofactor, thrombomodulin. TAFIa attenuates fibrinolysis. TAFIa can be inactivated by both proteolysis by thrombin and spontaneous temperaturedependent loss of activity. The identity of the thrombin cleavage site responsible for loss of TAFIa activity was suggested to be Arg 330 , but site-di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

6
124
0
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 21 publications
6
124
0
1
Order By: Relevance
“…Regulated by an intrinsic temperature-dependent instability (i.e., half-life of 10 min at 37°C, 45 min at 30°C, and several hours at 22°C, and stable at 0°C) [4], TAFIa is converted into an inactive conformation (TAFIai; 36 kDa). Furthermore, it has been shown that this intrinsic instability of TAFIa is of major importance for the in vivo downregulation of its activity [5][6][7]. The underlying structural mechanisms of this rapid and spontaneous loss of activity are still unclear, and this has complicated the study of the effect of TAFIa on fibrinolysis.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Regulated by an intrinsic temperature-dependent instability (i.e., half-life of 10 min at 37°C, 45 min at 30°C, and several hours at 22°C, and stable at 0°C) [4], TAFIa is converted into an inactive conformation (TAFIai; 36 kDa). Furthermore, it has been shown that this intrinsic instability of TAFIa is of major importance for the in vivo downregulation of its activity [5][6][7]. The underlying structural mechanisms of this rapid and spontaneous loss of activity are still unclear, and this has complicated the study of the effect of TAFIa on fibrinolysis.…”
mentioning
confidence: 99%
“…It could thus be expected that a 2 -AP deficiency would promote adipose tissue development. a 2 -AP is a 70 kDa single-chain glycoprotein that occurs in murine plasma at a concentration of about 90 lg mL )1 [6], and inhibits plasmin at a very high rate, similar to the human system [7]. Mice with inactivation of the a 2 -AP gene display a higher endogenous fibrinolytic potential than wild-type littermates [6].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, TAFIa is highly unstable, with reported halflives at 37°C of 8 -9 (7,8) and 15 min (9). Whereas TAFIa can also be cleaved by thrombin at Arg-302, this cleavage is subsequent to the spontaneous structural changes corresponding to inactivation of the enzyme (8,10) and is therefore probably not relevant to the regulation of the enzyme.…”
mentioning
confidence: 99%
“…TAFIa is a labile enzyme, with a half-life of Ͻ10 min at 37°C (7)(8)(9). TAFIa is inactivated by conformational instability, after which it becomes more susceptible to proteolytic degradation by thrombin (4,(7)(8)(9)(10)(11). Plasmin can inactivate TAFIa by proteolysis of the catalytic domain (12).…”
mentioning
confidence: 99%